Quasi one-dimensional (TaSe4) 2I and MoTe2 mixed-dimensional heterojunction phototransistor detector and preparation method thereof
By adopting a mixed dimensional heterostructure of quasi-one-dimensional (TaSe4)2I and two-dimensional MoTe2 in the photodetector, the problem of large dark current and low signal-to-noise ratio of the (TaSe4)2I photodetector is solved, and the photodetection effect with high responsiveness and high sensitivity is achieved.
Patent Information
- Application Number
- CN202510037859.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-09
AI Technical Summary
The photodetector based on the quasi-one-dimensional semi-metal material (TaSe4)2I has a problem of excessive dark current, resulting in low signal-to-noise ratio.
Using a mixed-dimensional heterostructure of quasi-one-dimensional (TaSe4)2I and two-dimensional MoTe2, carrier separation is accelerated through the vertical structure of the heterojunction, dark current is suppressed, and light absorption of the device is increased through MoTe2 to increase the photocurrent.
High responsiveness and high sensitivity photoelectric detection is achieved, which enhances the polarization detection capability of the device and improves the signal-to-noise ratio.
Smart Images

Figure CN119836020A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a phototransistor detector based on a quasi-one-dimensional (TaSe4)2I and two-dimensional MoTe2 mixed-dimensional composite structure, belonging to the technical field of low-dimensional materials and photoelectric functional devices. Technical Background
[0002] Polarization photodetectors can obtain higher resolution and more surface information of imaging targets in complex environments by identifying the polarization of light. They are currently widely used in military and civilian fields such as biological imaging, optical radar, night vision, and remote sensing. In recent years, anisotropic low-dimensional materials have been widely used to prepare polarization-sensitive photodetectors.
[0003] The crystal structure of quasi-one-dimensional materials contains a one-dimensional atomic chain. The intrinsic structural anisotropy leads to large anisotropy in their optoelectronic properties, making them excellent candidates for polarization photodetection devices. Among them, quasi-one-dimensional (TaSe4)2I is a type of Weyl semimetal material. (TaSe4)2I belongs to the tetragonal system and the I422 space group. [TaSe4] chains are arranged parallel to the c axis as the basic structural framework and are divided by iodine chains. Each [TaSe4] chain is composed of alternating Ta atoms and Se4 rectangles with four Se atoms on the corners. The low-symmetry crystal structure caused by [TaSe4] and II chains gives (TaSe4)2I significant anisotropic electrical, thermal and optical properties. In addition, the unique topological semimetal band structure gives (TaSe4)2I the advantages of high carrier mobility and ultra-wideband light absorption. In summary, due to the unique structural anisotropy and excellent optoelectronic properties of the quasi-one-dimensional semimetal (TaSe4)2I, it has important application prospects in the field of polarization optoelectronic devices.
[0004] However, due to the band structure of the (TaSe4)2I semimetal, the dark current of the photodetector based on (TaSe4)2I is very large, which seriously affects the signal-to-noise ratio of the device. Therefore, a unique device structure design is urgently needed to solve the problem of large dark current of (TaSe4)2I, so as to improve the comprehensive performance of the device such as sensitivity and switching ratio to meet the needs of practical applications.
[0005] Currently, van der Waals heterostructures based on low-dimensional materials have become promising candidates for next-generation electronic and optoelectronic devices due to their multifunctional device configurations and excellent optoelectronic properties. Compared with traditional single-material devices, heterostructure devices can make up for the shortcomings of single materials and broaden the possibilities of nanoscale functional devices. Therefore, building heterojunction devices is expected to solve the shortcoming of large dark current of quasi-one-dimensional (TaSe4)2I and realize high-performance polarization photodetectors. Summary of the invention
[0006] The present invention aims at the disadvantage that the dark current of the photodetector based on the quasi-one-dimensional semi-metal material (TaSe4)2I is too large, resulting in a low signal-to-noise ratio in terms of detection performance, and provides a phototransistor detector with a mixed dimensional heterostructure of quasi-one-dimensional (TaSe4)2I and two-dimensional MoTe2, which has excellent performance, can suppress the large dark current of (TaSe4)2I, and improve the photocurrent of the device. At the same time, a preparation method of the phototransistor detector is provided. The vertical structure of the heterojunction can accelerate the separation of carriers and suppress the dark current; at the same time, MoTe2 increases the light absorption of the device and increases the photocurrent of the device. The photocurrent can be further increased by regulating the gate voltage. Therefore, the phototransistor detector based on the (TaSe4)2I / MoTe2 heterojunction has a high responsiveness and can achieve high-sensitivity photodetection. In addition, due to the increase in the carrier separation efficiency, the polarization detection capability of the device can also be enhanced.
[0007] The quasi-one-dimensional (TaSe4)2I and two-dimensional MoTe2 composite structure phototransistor detector of the present invention adopts the following technical scheme:
[0008] The composite structure phototransistor detector includes Si substrate, SiO2 gate dielectric layer, quasi-one-dimensional (TaSe4)2I and two-dimensional MoTe2 nanofilm from bottom to top, and metal electrodes are respectively arranged on the quasi-one-dimensional (TaSe4)2I and MoTe2 nanofilms to form a heterostructure of (TaSe4)2I, MoTe2 and metal electrodes. The mixed-dimensional heterojunction (TaSe4)2I / MoTe2 is used as the channel material, and Si substrate and SiO2 are used as the gate dielectric layer. The gate voltage is applied to silicon to regulate the photocurrent.
[0009] The thickness of the [TaSe4]2I nanowire is 50 to 200 nm.
[0010] The Si substrate is a heavily doped P-type silicon wafer with a surface SiO2 thickness of 280-300nm.
[0011] The MoTe2 nanofilm has a thickness of 30 to 100 nm.
[0012] The metal electrodes are 3-5 nm chromium and 30-50 nm gold.
[0013] The above detector combines (TaSe4)2I and MoTe2 together through van der Waals forces to form a (TaSe4)2I / MoTe2 mixed-dimensional heterojunction. On the one hand, the vertical structure of this heterojunction can improve the separation efficiency of carriers and suppress the large dark current of (TaSe4)2I; on the other hand, MoTe2 increases the light absorption of the device and improves the photocurrent of the device. High photocurrent and low dark current make the one-dimensional (TaSe4)2I and two-dimensional MoTe2 mixed-dimensional heterojunction phototransistor have ultra-sensitive photodetection performance. In addition, the large anisotropy and ultra-wideband response of (TaSe4)2I will give the heterojunction phototransistor polarization detection capability and visible-infrared broadband detection capability.
[0014] The method for preparing the above-mentioned quasi-one-dimensional [TaSe4]2I and two-dimensional MoTe2 composite structure phototransistor photodetector comprises the following steps:
[0015] (1) Transferring [TaSe4]2I nanowires onto Si substrate;
[0016] The specific process is: [TaSe4]2I nanowires are transferred to a Si substrate with a SiO2 surface using polydimethylsiloxane (PDMS) tape.
[0017] (2) Transferring the MoTe2 nanofilm to one side of the [TaSe4]2I nanowire already placed on the Si substrate;
[0018] (3) Spin-coating photoresist uniformly on the surface of the Si substrate to prepare the pattern of the bottom electrode;
[0019] The rotation speed of the spin-coated photoresist is 3500-4500 rpm, and the spinning time is 30-40 seconds.
[0020] (4) Positioning and exposing the bottom electrode pattern, and then developing it to expose the portion where the electrode needs to be deposited;
[0021] (5) preparing metal electrodes;
[0022] The preparation process of [TaSe4]2I nanowires in step (1) is:
[0023] ① Prepare the ingredients according to the molar ratio of Ta:Se:I=2:8~8.1:1~2, put them into a quartz tube and mix them evenly, sinter and seal the tube after vacuuming;
[0024] The vacuum degree of the vacuum pumping is 3 to 5×10 -4 Pa.
[0025] ② Place the quartz tube in a heating furnace and raise the temperature in stages to allow the raw materials to fully react;
[0026] The staged heating is firstly to heat to 120-150° C. for 10-15 hours and keep the temperature constant for 5-20 hours; then to heat to 600-700° C. for 10-25 hours and keep the temperature constant for 25-35 hours.
[0027] ③After the reaction is completed, the temperature of the heating furnace body is reduced to 400-500°C, and then reduced to room temperature after 5-10 hours of constant temperature;
[0028] The furnace body is cooled at a rate of 0.2-2°C / hour.
[0029] ④ Take out the [TaSe4]2I bulk single crystal, place it in alcohol, remove the I attached to the surface, and then clean it with deionized water;
[0030] ⑤ Mechanically exfoliate the [TaSe4]2I bulk single crystal to prepare [TaSe4]2I nanowires;
[0031] The specific process is: transfer the [TaSe4]2I bulk single crystal to Scotch tape, and then repeatedly fold and paste the tape. As the number of pastings increases, quasi-one-dimensional [TaSe4]2I nanowires of different thicknesses are continuously peeled off. The thinner the [TaSe4]2I nanowire, the lighter the color. As the color of the sample on the tape surface gradually becomes lighter, the bulk single crystal on the tape will be separated into thinner [TaSe4]2I nanowires.
[0032] The performance index of the [TaSe4]2I and MoTe2 composite structure device prepared by the above method was tested using a semiconductor test system. A 440nm light source was used as the excitation light source. Under a bias voltage of 3V and a gate voltage of -10V, the device's responsivity was as high as 40A / W. Under a bias voltage of -3V, the polarization ratio reached 3.6.
[0033] Although there are photoelectric devices with composite structures of MoTe2 and other two-dimensional materials, their device performance is far inferior to the [TaSe4]2I and MoTe2 composite structure phototransistor detector prepared by the present invention.
[0034] The [TaSe4]2I and MoTe2 composite structure phototransistor detector of the present invention has achieved outstanding implementation effects compared with other heterojunction photodetectors. Compared with the photodetector using only [TaSe4]2I, it shows higher responsivity, external quantum efficiency, detection rate, and polarization ratio (see Polarization-Sensitive PhotodetectorBased on Quasi-1D(TaSe4)2I Nanowire Response to 10.6μm, Adv.Funct.Mater.2024,34,2315194.). Compared with the photodetector using only MoTe2, it also shows better responsivity and detection rate (see Highly sensitive visible to infrared MoTe2 photodetectors enhanced by thephotogating effect, Nanotechnology 2016,27,445201.). Compared with other (quasi) one-dimensional / two-dimensional mixed-dimensional heterojunctions (such as WS2 / 1DSb2Se3, MoS2 / 1D Ta2Pd3Se8, and MoS2 / 1D GaAsSb), the heterojunction phototransistor detector of the present invention also exhibits better sensitivity characteristics (see Direct van der Waals epitaxial growthof 1D / 2D Sb2Se3 / WS2mixed-dimensional pn heterojunctions, Nano Res. 2019, 12, 1139; Ultrafast Polarization Sensitive Photodetector Based on MoS2 / Ta2Pd3Se8Hybrid Dimensional Heterostructure, Adv. Optic. Mater. 2023, 11, 2300593; Mixed-Dimensional Anti-ambipolar Phototransistors Based on 1D GaAsSb / 2D MoS2Heterojunctions, ACS Nano 2022, 16, 11036).
[0035] Table 1 shows the comparison of the detector performance of the [TaSe4]2I and MoTe2 composite structure phototransistor detector of the present invention and other heterojunction photodetectors.
[0036] Table 1 Performance comparison of photodetectors with different 2D materials and structures
[0037]
[0038] The present invention utilizes the characteristics of high carrier mobility and full spectrum response of the quasi-one-dimensional semi-metal material (TaSe4)2I, introduces the two-dimensional material MoTe2 to increase light absorption, and increases the carrier separation efficiency through the vertical structure of the heterojunction, thereby suppressing the dark current, and solving the shortcomings of large dark current and small switching ratio of the single material (TaSe4)2I photodetector. Furthermore, through the back-gate phototransistor structure, the transport characteristics of the channel carriers are regulated, and the photocurrent is increased to the μA level under negative gate voltage, thereby obtaining extremely high responsiveness and external quantum efficiency, thereby greatly improving the sensitivity of the device and having the ability of ultra-sensitive detection. In addition, due to the improvement of the carrier separation efficiency of the heterostructure, the polarization detection capability of the heterojunction photodetector is greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 It is a schematic structural diagram of the quasi-one-dimensional (TaSe4)2I and two-dimensional MoTe2 composite structure phototransistor detector of the present invention.
[0040] Figure 2 This is an optical image of the quasi-one-dimensional (TaSe4)2I and two-dimensional MoTe2 composite structure phototransistor detector of the present invention.
[0041] Figure 3 The quasi-one-dimensional (TaSe4)2I and two-dimensional MoTe2 composite structure prepared in Example 1 ( Figure 1 Dashed box 8) and (TaSe4)2I device structure ( Figure 1 Dashed box 6) and MoTe2 device structure ( Figure 1 The dark current output characteristic curve comparison diagram of the dotted box 7). The current value of (TaSe4)2I corresponds to the left Y axis, and the current value of MoTe2 and (TaSe4)2I / MoTe2 mixed-dimensional heterojunction corresponds to the right Y axis.
[0042] Figure 4 This is a photocurrent diagram of the quasi-one-dimensional (TaSe4)2I and two-dimensional MoTe2 composite structure phototransistor detector prepared in Example 1 under different gate voltages.
[0043] Figure 5 This is a graph of the responsivity and detectivity of the quasi-one-dimensional (TaSe4)2I and two-dimensional MoTe2 composite structure phototransistor detector prepared in Example 1 under a gate voltage of -10V and a bias voltage of 3V.
[0044] Figure 6This is a time-current (IT) diagram of the polarization light angle dependence of the quasi-one-dimensional (TaSe4)2I and two-dimensional MoTe2 composite structure phototransistor detector prepared in Example 1 under a -3V bias.
[0045] Among them: 1. Si substrate, 2. SiO2 gate dielectric layer, 3. (TaSe4)2I nanowire, 4. MoTe2 nanofilm, 5. Metal electrode, 6. (TaSe4)2I single material device, 7. MoTe2 single material device, 8. (TaSe4)2I / MoTe2 heterojunction device, 9. Laser. DETAILED DESCRIPTION
[0046] like Figure 1 As shown, the quasi-one-dimensional (TaSe4)2I and two-dimensional MoTe2 composite structure phototransistor detector of the present invention comprises, from bottom to top, a Si substrate 1, a SiO2 gate dielectric layer 2, a (TaSe4)2I nanowire 3 and a MoTe2 nanofilm 4, on which a metal electrode 5 is arranged. The MoTe2 nanofilm 4 is placed on the right side of the (TaSe4)2I nanowire 3. The Si substrate 1 is a heavily doped P-type silicon wafer with a surface SiO2 thickness of 280 to 300 nm, the thickness of the [TaSe4]2I nanowire 3 is 50 to 200 nm, the thickness of the MoTe2 nanofilm 4 is 30 to 100 nm, and the metal electrode 5 is 3 to 5 nm chromium and 30 to 50 nm gold. The (TaSe4)2I nanowire 3 and a pair of electrodes thereon constitute a (TaSe4)2I single material device 6. The MoTe2 nanofilm 4 and a pair of electrodes thereon constitute a MoTe2 single material device 7. An electrode on the (TaSe4)2I nanowire 3 and an electrode on the MoTe2 nanofilm 4 form a (TaSe4)2I / MoTe2 heterojunction device 8 (ie, the composite structure phototransistor detector in the present invention).
[0047] Figure 2 The optical image of the quasi-one-dimensional (TaSe4)2I and two-dimensional MoTe2 composite structure phototransistor detector of the present invention is given. The electrode pattern can be composed of three pairs of electrodes, one pair of which is designed on the (TaSe4)2I nanowire 3 (see Figure 1 A pair of electrodes in the dotted box indicated by the mark 6 in the figure) and a pair of electrodes designed on the MoTe2 film 4 (see Figure 1 A pair of electrodes in the dotted box indicated by the mark 7 in FIG. 1 ) are designed on the (TaSe4)2I nanowire 3 and the MoTe2 film 4 respectively (see Figure 1 A pair of electrodes within the dotted box indicated by mark 8 in FIG.
[0048] The two-dimensional MoTe2 nanofilm 4 is placed on one side of the (TaSe4)2I nanowire 3, and the (TaSe4)2I / MoTe2 composite structure is used to suppress dark current. Silicon is used as the substrate and SiO2 as the gate dielectric layer, and gate voltage is applied to silicon to regulate the photocurrent. Thus, an ultra-sensitive photodetector device is realized.
[0049] The specific preparation process of the (TaSe4)2I / MoTe2 phototransistor of the present invention is described in detail below in conjunction with the accompanying drawings and examples.
[0050] Example 1
[0051] In this embodiment, a phototransistor detector having a composite structure of a (TaSe4)2I nanowire 3 (TaSe4)2I with a thickness of 98 nm and a MoTe2 nanofilm 4 with a thickness of 68 nm is prepared.
[0052] (1) Prepare the ingredients according to the molar ratio of Ta:Se:I = 2:8.02:1.2, then put the raw materials into a quartz tube and evacuate to 3×10 -4 After pa, sinter and seal the tube.
[0053] (2) The quartz tube is placed in a heating furnace and the temperature is raised in stages. First, the temperature is raised to 120°C over 10 hours and kept at this temperature for 15 hours; then the temperature is raised to 660°C over 15 hours and kept at this temperature for 25 hours.
[0054] (3) Slowly cool the temperature to 500°C at a rate of 0.2°C / hour, during which (TaSe4)2I nucleates and grows; after keeping the temperature constant for 5 hours, cool the temperature to room temperature to obtain a (TaSe4)2I bulk single crystal.
[0055] (4) After breaking the quartz tube, the (TaSe4)2I bulk single crystal was taken out and placed in ethanol to remove the raw material I attached to the surface. The crystal was then cleaned with deionized water to obtain a needle-shaped (TaSe4)2I bulk crystal with a metallic luster.
[0056] (5) Select high-quality (TaSe4)2I bulk single crystals, then repeatedly fold and stick the tape (no need to remove and stick the sample). As the color of the sample on the tape surface gradually becomes lighter, the bulk single crystals on the tape will be separated into thinner (TaSe4)2I nanowires. Until a (TaSe4)2I nanowire with a thickness of 98nm is obtained.
[0057] (6) The (TaSe4)2I nanowires prepared by the above method were transferred to a heavily doped P-type silicon wafer with a surface layer of 290 nm thick SiO2 using PDMS tape.
[0058] (7) The MoTe2 was mechanically exfoliated using the same Scotch tape as in step (5) to obtain a 68 nm thick MoTe2 nanofilm.
[0059] (8) A portion of the obtained MoTe2 nanofilm is transferred to one side of the (TaSe4)2I nanowire 3 already placed on the Si substrate using a transfer platform (see Figure 1 The other part of the MoTe2 nanofilm is directly placed on the SiO2 substrate 2 (see Figure 1 The dotted box indicated by mark 7 in FIG.
[0060] (9) Spin AZ1500 photoresist onto the sample obtained in step (8) above using a spin coater and design and prepare an electrode pattern at a spin coater speed of 4000 rpm for 30 s.
[0061] For performance comparison, the electrode pattern can be composed of three pairs of electrodes, one pair of which is designed on the (TaSe4)2I nanowire 3 (see Figure 1 A pair of MoTe2 nanofilms 4 are designed on the dotted box indicated by the marker 6 in FIG. Figure 1 The dotted box indicated by the marker 7 in the figure), an electrode on (TaSe4)2I and an electrode on MoTe2 form a pair of electrodes of the (TaSe4)2I / MoTe2 mixed-dimensional heterojunction (see Figure 1 The dotted box indicated by the mark 8 in FIG.
[0062] (10) The electrode pattern is exposed using a laser direct writing lithography machine to prepare the electrode, and then developed using AZ400K developer to expose the electrode pattern.
[0063] (11) The samples obtained above were used to prepare metal electrodes using existing thermal evaporation technology, first evaporating 3 nm of chromium and then evaporating 50 nm of gold.
[0064] Figure 3 The photocurrent output characteristic curve of the (TaSe4)2I / MoTe2 composite structure phototransistor detector prepared in this embodiment is given, which is different from the photocurrent output characteristic curve of the (TaSe4)2I device structure ( Figure 1 Dashed box 6) and only MoTe2 device structure ( Figure 1 The dark current output characteristic curve of the dashed box 7) is compared. Figure 3 It can be seen that the dark current increases with the increase of voltage, and under the same test conditions, the (TaSe4)2I / MoTe2 composite structure has a lower dark current than (TaSe4)2I and MoTe2.
[0065] Figure 4 The photocurrent diagram of the (TaSe4)2I / MoTe2 composite structure phototransistor detector prepared in this example at different gate voltages is given. Figure 4It can be seen that under the same test conditions, the net photocurrent is larger under negative gate voltage than under zero gate voltage, and increases with the increase of negative gate voltage.
[0066] The (TaSe4)2I / MoTe2 composite structure phototransistor detector prepared in this embodiment was tested for performance indicators using a semiconductor testing system. Figure 5 The responsivity and detection rate of the (TaSe4)2I / MoTe2 composite structure phototransistor detector prepared in this example at different gate voltages are given, using a 440nm wavelength laser 9 (see Figure 1 ) as the excitation light source, at a bias voltage of 3V and a gate voltage of -10V, the device has a high responsivity of 40A / W and a detection rate of 2.1×10 12 Jones.
[0067] Figure 6 The polarization detection capability of the (TaSe4)2I / MoTe2 composite structure phototransistor detector prepared in this example is demonstrated. ... Figure 1 ) light source as the excitation light source. Under a bias voltage of -3 V, the output current changes with the change of the polarization angle, and the polarization current ratio reaches 3.6.
[0068] Example 2
[0069] In this embodiment, a phototransistor detector having a composite structure of a (TaSe4)2I nanowire 3 with a thickness of 110 nm and a MoTe2 nanofilm 4 with a thickness of 47 nm is prepared.
[0070] (1) Prepare the ingredients according to the molar ratio of Ta:Se:I = 2:8.05:1.5, then put the raw materials into a quartz tube and evacuate to 4×10 -4 After pa, sinter and seal the tube.
[0071] (2) The quartz tube is placed in a heating furnace and the temperature is raised in stages. First, the temperature is raised to 150°C for 12 hours and kept constant for 5 hours; then the temperature is raised to 600°C for 20 hours and kept constant for 30 hours.
[0072] (3) Slowly cool the temperature to 450°C at a rate of 1°C / hour, during which (TaSe4)2I nucleates and grows; after keeping the temperature constant for 8 hours, cool the temperature to room temperature to obtain a (TaSe4)2I bulk single crystal.
[0073] (4) After breaking the quartz tube, the (TaSe4)2I bulk single crystal was taken out and placed in ethanol to remove the raw material I attached to the surface. The crystal was then cleaned with deionized water to obtain a needle-shaped (TaSe4)2I bulk crystal with a metallic luster.
[0074] (5) Select high-quality MoTe2 bulk single crystals and use Scotch tape for mechanical exfoliation. Repeatedly fold and paste the tape multiple times to obtain 110nm (TaSe4)2I nanowires.
[0075] (6) The (TaSe4)2I nanowires prepared by the above method were transferred to a heavily doped P-type silicon wafer with a surface layer of 280 nm thick SiO2 using PDMS tape.
[0076] (7) The MoTe2 was mechanically exfoliated using the same Scotch tape as in step (5) to obtain a 47 nm thick MoTe2 nanofilm.
[0077] (8) The obtained MoTe2 nanofilm is transferred to one side of the MoTe2 nanowire placed on the Si substrate with the assistance of a transfer platform.
[0078] (9) Spin-coat AZ1500 photoresist on the sample obtained in step (8) above with a spin coater and design and prepare an electrode pattern at a spin coater speed of 3500 rpm for 40 seconds.
[0079] (10) The electrode pattern is exposed using a laser direct writing lithography machine to prepare the electrode, and then developed using AZ400K developer to expose the electrode pattern.
[0080] (11) The samples obtained above were used to prepare metal electrodes using thermal evaporation technology, first evaporating 4 nm chromium and then evaporating 40 nm gold.
[0081] Example 3
[0082] In this embodiment, a phototransistor detector having a composite structure of (TaSe4)2I nanowires 3 with a thickness of 160 nm and MoTe2 nanofilms 4 with a thickness of 88 nm is prepared.
[0083] (1) Prepare the ingredients according to the molar ratio of Ta:Se:I = 2:8.08:1.9, then put the raw materials into a quartz tube and evacuate to 5×10 -4 After pa, sinter and seal the tube.
[0084] (2) The quartz tube is placed in a heating furnace and the temperature is raised in stages. First, the temperature is raised to 135°C over 15 hours and kept constant for 20 hours; then the temperature is raised to 700°C over 25 hours and kept constant for 35 hours.
[0085] (3) Slowly cool the temperature to 400°C at a rate of 2°C / hour, during which (TaSe4)2I nucleates and grows; after maintaining the temperature for 10 hours, cool the temperature to room temperature to obtain a (TaSe4)2I bulk single crystal.
[0086] (4) After breaking the quartz tube, the (TaSe4)2I bulk single crystal was taken out and placed in ethanol to remove the raw material I attached to the surface. The crystal was then cleaned with deionized water to obtain a needle-shaped (TaSe4)2I bulk crystal with a metallic luster.
[0087] (5) Select high-quality (TaSe4)2I bulk single crystals and use Scotch tape to mechanically peel them off. The tape is repeatedly folded and pasted multiple times to obtain 160nm (TaSe4)2I nanowires.
[0088] (6) The (TaSe4)2I nanofilm prepared by the above method was transferred to a heavily doped P-type silicon wafer with a surface thickness of 300 nm SiO2 using PDMS tape.
[0089] (7) The MoTe2 was mechanically exfoliated using the same Scotch tape as in step (5) to obtain a MoTe2 nanofilm with a thickness of 88 nm.
[0090] (8) The obtained MoTe2 nanofilm is transferred to one side of the (TaSe4)2I nanowire placed on the Si substrate with the assistance of a transfer platform.
[0091] (9) Spin-coat AZ1500 photoresist on the sample obtained in step (8) above with a spin coater and design and prepare an electrode pattern at a spin coater speed of 4500 rpm for 35 s.
[0092] (10) The electrode pattern is exposed using a laser direct writing lithography machine to prepare the electrode, and then developed using AZ400K developer to expose the electrode pattern.
[0093] (11) The samples obtained above were used to prepare metal electrodes using thermal evaporation technology, first evaporating 5 nm of chromium and then evaporating 30 nm of gold.
[0094] Example 4
[0095] In this embodiment, a phototransistor detector having a composite structure of (TaSe4)2I nanowires 3 with a thickness of 200 nm and MoTe2 nanofilms 4 with a thickness of 100 nm is prepared.
[0096] The preparation process is the same as that of Example 3, except that in step (5) a (TaSe4)2I nanowire with a thickness of 200 nm is obtained, and in step (7) a MoTe2 nanofilm with a thickness of 100 nm is obtained.
[0097] Example 5
[0098] In this embodiment, a phototransistor detector having a composite structure of a 50 nm thick ((TaSe4)2I nanowire 3 and a 30 nm thick MoTe2 nanofilm 4 is prepared.
[0099] The preparation process is the same as that of Example 3, except that in step (5) a (TaSe4)2I nanowire with a thickness of 50 nm is obtained, and in step (7) a MoTe2 nanofilm with a thickness of 30 nm is obtained.
Claims
1. A quasi-one-dimensional (TaSe4)2I and two-dimensional MoTe2 mixed-dimensional heterojunction phototransistor detector, characterized in that: From bottom to top, it includes Si substrate, SiO2 gate dielectric layer, quasi-one-dimensional (TaSe4)2I and two-dimensional MoTe2 nanofilm. Metal electrodes are respectively arranged on the quasi-one-dimensional (TaSe4)2I and MoTe2 nanofilm to form a heterostructure of (TaSe4)2I, MoTe2 and metal electrodes.
2. The quasi-one-dimensional (TaSe4)2I and two-dimensional MoTe2 mixed-dimensional heterojunction phototransistor detector according to claim 1, characterized in that: The thickness of the (TaSe4)2I nanowire is 50-200nm.
3. The quasi-one-dimensional (TaSe4)2I and two-dimensional MoTe2 mixed-dimensional heterojunction phototransistor detector according to claim 1, characterized in that: The Si substrate is a heavily doped P-type silicon wafer with a surface SiO2 thickness of 280-300nm.
4. The quasi-one-dimensional (TaSe4)2I and two-dimensional MoTe2 mixed-dimensional heterojunction phototransistor detector according to claim 1, characterized in that: The MoTe2 nanofilm has a thickness of 30 to 100 nm.
5. The quasi-one-dimensional (TaSe4)2I and two-dimensional MoTe2 mixed-dimensional heterojunction phototransistor detector according to claim 1, characterized in that: The metal electrodes are 3-5 nm chromium and 30-50 nm gold.
6. A method for preparing a quasi-one-dimensional (TaSe4)2I and two-dimensional MoTe2 mixed-dimensional heterojunction phototransistor detector according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) Transferring (TaSe4)2I nanowires to Si substrate; (2) Transferring the MoTe2 nanofilm to one side of the (TaSe4)2I nanowire already placed on the Si substrate; (3) Spin-coating photoresist uniformly on the surface of the Si substrate to prepare the pattern of the bottom electrode; (4) Positioning and exposing the bottom electrode pattern, and then developing it to expose the portion where the electrode needs to be deposited; (5) Preparation of metal electrodes.
7. The method for preparing the quasi-one-dimensional (TaSe4)2I and two-dimensional MoTe2 mixed-dimensional heterojunction phototransistor detector according to claim 6, characterized in that: The preparation process of [TaSe4]2I nanowires in step (1) is: ① Prepare the ingredients according to the molar ratio of Ta:Se:I=2:8~8.1:1~2, put them into a quartz tube and mix them evenly, sinter and seal the tube after vacuuming; ② Place the quartz tube in a heating furnace and raise the temperature in stages to allow the raw materials to fully react; The staged heating is firstly to heat to 120-150° C. for 10-15 hours and keep the temperature constant for 5-20 hours; then to heat to 600-700° C. for 10-25 hours and keep the temperature constant for 25-35 hours. ③After the reaction is completed, the temperature of the heating furnace body is reduced to 400-500°C, and then reduced to room temperature after 5-10 hours of constant temperature; ④ Take out the [TaSe4]2I bulk single crystal, place it in alcohol, remove the I attached to the surface, and then clean it with deionized water; ⑤ Mechanically exfoliate the [TaSe4]2I bulk single crystal to prepare [TaSe4]2I nanowires.
8. The method for preparing the quasi-one-dimensional (TaSe4)2I and two-dimensional MoTe2 mixed-dimensional heterojunction phototransistor detector according to claim 7, characterized in that: The specific process of step ⑤ is: transferring the [TaSe4]2I bulk single crystal to Scotch tape, and then repeatedly folding and pasting the tape. As the number of pastings increases, quasi-one-dimensional [TaSe4]2I nanowires of different thicknesses are continuously peeled off, and the thinner the [TaSe4]2I nanowires, the lighter the color. As the color of the sample on the tape surface gradually becomes lighter, the bulk single crystal on the tape will be separated into thinner [TaSe4]2I nanowires.
9. The method for preparing a quasi-one-dimensional (TaSe4)2I and two-dimensional MoTe2 mixed-dimensional heterojunction phototransistor detector according to claim 6, characterized in that: The specific process of transferring the [TaSe4]2I nanowires to the Si substrate in step (1) is as follows: transferring the [TaSe4]2I nanowires to the Si substrate with the surface being SiO2 with the assistance of polydimethylsiloxane (PDMS) tape.
10. The method for preparing the quasi-one-dimensional (TaSe4)2I and two-dimensional MoTe2 mixed-dimensional heterojunction phototransistor detector according to claim 6, characterized in that: In the step (3), the rotation speed of the spin-coating photoresist is 3500 to 4500 rpm, and the spinning time is 30 to 40 seconds.
Citation Information
Patent Citations
Method for increasing the switch ratio of graphene and nanowire heterojunction detector
CN104538489A
Mixed-dimension Sn-CdS / molybdenum telluride heterojunction-based photoelectric detector and preparation method thereof
CN114497248A
Cited By
Semi-metal MoTe2 modification method and photoelectric detector based on modified semi-metal MoTe2
CN120583769A
Weyl semimetal / TMDC heterojunction photoelectric detector and application thereof
CN121057314A
A weyl semimetal / tmcd heterojunction photodetector and application thereof
CN121057314B